Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

The simplest example of this is $e^x$ which we could say has period 1 (it is its own derivative). $e^{-x}$ would have period 2.

Using similar constructions, I can get a function that has a derivative of period $n$ by doing $e^{x\cdot (1)^{1/n}}$

Is this the only way to get periodic derivatives?

Note: I am treating sin and cos as special cases of this when $n=4$

Is there a proof to this effect?

share|improve this question
3  
The space of functions satisfying $f^{(n)}=f$ has dimension $n$ (dimensions of solution spaces is an important consideration in differential equations), and there are $n$ distinct $n$th roots of unity. –  anon Sep 9 '12 at 7:05
1  
There aren't any. –  André Nicolas Sep 9 '12 at 7:06
    
@AndréNicolas why not though? –  soandos Sep 9 '12 at 7:07
    
The answer is presumably being typed by anon. If not, recall how to solve linear homogeneous DE with constant coefficients. –  André Nicolas Sep 9 '12 at 7:10
1  
The other thing to note is that a solution to a differential equation of order $n$ is determined by initial conditions on $y, y', \ldots, y^{(n-1)}$, and therefore the space of solutions has dimension $n$. Thus once you have solutions of the form $e^{\lambda x}$ for $n$ different $\lambda$ (and these are easily seen to be linearly independent), all solutions are linear combinations of these. –  Robert Israel Sep 9 '12 at 7:24

1 Answer 1

up vote 2 down vote accepted

Assume $f^{(n)}(x)=f(x)$ for all $x$. Let $g(x) = \sum_{k=0}^{n-1}\xi^{-k} f^{(k)}(x)$, where $\xi^n=1$. Then $g'(x)=\sum_{k=0}^{n-1}\xi^{-k} f^{(k+1)}(x) = \xi\sum_{k=1}^{n}\xi^{-k} f^{(k)}(x)=\xi g(x)$. We already know all solutions of $y'=c y$ and conclude that $g(x)=a e^{\xi x}$.

If we additionally assume that $\xi$ is primitive, we find for $0\le m<n$ that $$ \sum_{k=0}^{n-1}\xi^{-mk} f^{(k)}(x)= a_m e^{\xi^m x}$$ Adding all equations leads to $$n f(x) = \sum_{m=0}^{n-1} a_m e^{\xi^m x}.$$

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.